Randomized controlled trial of SecondStory, an intervention targeting posttraumatic growth, with bereaved adults - Roepke, Ann Marie; Forgeard, Marie, J.C.; Tsukayama, Eli; Blackie, Laura E.R.; Jayawickreme, Eranda (American Psychological Association, 2018)
Objective: People often report positive psychological changes after adversity, a phenomenon known as posttraumatic growth (PTG). Few PTG-focused interventions have been rigorously tested, and measurement strategies have had significant limitations. This study evaluated the effects of a new group-format psychosocial intervention, SecondStory, aimed at facilitating PTG by helping participants make meaning of the past and plan a purposeful future. Method: In a randomized controlled trial, adults (N = 112, 64% women) bereaved within five years were randomly assigned to SecondStory or an active control, expressive writing. The primary outcome, PTG, was measured using two contrasting methods: the Posttraumatic Growth Inventory, which asks participants retrospectively how much they believe they have changed due to struggling with adversity, and the Current-Standing Posttraumatic Growth Inventory, which tracks quantifiable change in participants’ standing in PTG domains over time. Secondary outcomes included depression symptoms, posttraumatic stress symptoms, and life satisfaction. Outcomes were measured at two-week intervals: pre-test, post-test, and three follow-up occasions. Hierarchical linear modeling was used to assess whether SecondStory participants experienced greater gains in primary and/or secondary outcomes over the eight-week trial. Results: Results indicated that SecondStory participants did not show significantly greater improvements than control participants on measures of PTG, posttraumatic stress, or life satisfaction, but did show greater decreases in depression symptoms by the first follow-up.